Retrospective Analysis of Healthcare Resource Use, Treatment Patterns, and Treatment-related Events in Patients with Huntington’s Disease–associated Chorea Initiated on Tetrabenazine - Victor W. Sung; Sanjay K. Gandhi; Victor Abler; Brian Davis; Debra E. Irwin; Karen E. Anderson; Ravi G. Iyer (Journal of Health Economics and Outcomes Research)
**Background:** Huntington’s disease (HD) is a multifaceted neurodegenerative disorder characterized by involuntary movements, specifically chorea, as well as behavioral and psychiatric disturbance, and cognitive dysfunction. Tetrabenazine was the first approved treatment for chorea, although tolerability concerns exist.